2019
DOI: 10.1039/c9ra06678k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in metallopolymer-based drug delivery systems

Abstract: The recent (over the past five years) advances and problems associated with the use of metallopolymers as drug delivery systems (DDSs) are presented and assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 297 publications
(318 reference statements)
1
14
0
Order By: Relevance
“…While the PFcMA 126 ‐F127‐PFcMA 126 nanofibers, it exhibits broad diffraction peaks at 2θ = 12.5°‐18.5° comparison to the polymer with many diffraction peaks at 2θ = 7.5°‐40°, showing the nanofibers is amorphous. Besides the orientation in electrospinning, crystallization is resulting from the phase separation of F127 block and backbone of the ferrocene‐containing side chain and eutectic of the chain fragment in multi‐block copolymer, 44–45,56 which is agreed with the DSC measurement.…”
Section: Resultssupporting
confidence: 68%
“…While the PFcMA 126 ‐F127‐PFcMA 126 nanofibers, it exhibits broad diffraction peaks at 2θ = 12.5°‐18.5° comparison to the polymer with many diffraction peaks at 2θ = 7.5°‐40°, showing the nanofibers is amorphous. Besides the orientation in electrospinning, crystallization is resulting from the phase separation of F127 block and backbone of the ferrocene‐containing side chain and eutectic of the chain fragment in multi‐block copolymer, 44–45,56 which is agreed with the DSC measurement.…”
Section: Resultssupporting
confidence: 68%
“…28,29,[33][34][35] Functional polypyrrole lms containing metal complex units have been reported for various applications, e.g., catalytic reactions, sensors, and drug delivery. 28,29,[33][34][35][36][37][38][39][40][41] Deronzier et al reported that a system with a polypyrrole layer containing a Re(I) complex catalyst on Pt electrodes showed higher durability for electrocatalytic CO 2 reduction than the system with the corresponding mononuclear Re(I) complex in solution. 33,36,42 Morikawa et al deposited a polypyrrole layer containing a Ru(II) complex catalyst onto a p-type semiconductor photoelectrode, i.e., used a method of the rst type according to the abovementioned classication.…”
Section: Introductionmentioning
confidence: 99%
“…The past decades witnessed the rapid development of ferrocenyl (Fc)‐containing polymers and their functional applications in various fields, [ 1–3 ] such as drug delivery, [ 4,5 ] magneto‐ceramics, [ 6 ] electro‐chromics, [ 7 ] hydrogels, [ 8–10 ] biomaterials, [ 11 ] sensors, [ 12,13 ] catalysis, [ 14 ] and stimuli‐responsive materials. [ 15 ] Especially, the elegant application of ring‐opening polymerization (ROP) of strained silicon‐bridged [ 1 ] ferrocenophane monomers led to a whole field of chemistry poly (ferrocenylsilanes) (PFS)‐based main‐chain Fc‐containing polymers.…”
Section: Introductionmentioning
confidence: 99%